FAKTOR-FAKTOR PENGHAMBAT IMPLEMENTASI KERJASAMA INDONESIA DAN NORWEGIA DALAM SKEMA REDD+ DI KABUPATEN KAPUAS PROVINSI KALIMANTAN TENGAH (2013-2015) - Aprillia, Dwi Monica; ", Pazli (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
This research aims to explain the factors that obstruction implementation of cooperation between Indonesia and Norway in the scheme Reduction Emission from Deforestation and Degradation Plus (REDD+) in Kapuas, Central Kalimantan (2013-2015). REDD+ is the provision of incentives to rainforest nations to protect their forests in order to reduce greenhouse gas emissions, protection sustainable management of forests and enhancement of carbon reserves. Norway support this program through a Letter of Intent (LOI) in cooperation to reduce emission from deforestation and forest degradation in Indonesia. Indonesian government has commited to reducing emission from deforestation and forest degradation by targeting deforestation to 26-40 % in 2020, and has started the preparation process for REDD+ at the national and subnational level. Afterwards Indonesia choose Central Kalimantan as location pilot project to implementation programe. The result shows that implementation of REDD+ programe in Kapuas, Central Kalimantan is not effective yet. It causes by internal factors such as problem in scheme of REDD and problem in indigeneous people in Central Kalimantan. And external factors such as dispersion of BP REDD, dispersion of DNPI, and problem in forest moratorium.Keywords: REDD+, Implementation Programme, Kapuas District, Indonesia, Norwegia.